REDUCE WATER CONSUMPTION BY ALTERNATIVE DISPOSAL OF PHYSIOLOGICAL WASTE HUMAN - Ремез, Н. С.; Бойко, А. Г. (Science-based technologies, 2017)
This article is about needs of conservation and rational use of water resources, the relevance of which is the shortage of fresh water is one of the major problems of mankind. The base of research is technology of reduce water consumption though the use of eco-sanitary devices of saving water, where physiological human waste processed into fertilizer for crops as a result of their composting and sedimentation.The use of this equipment leads to a reduction of water resources, which causes the relevance of research in this area, therefore, conducted comparative calculation of consumption and pollution of water in the absence and presence of eco-sanitary devices water conservation, that is, the analysis of the ecological load on used fresh water without and with this eco-sanitation technology.